Web-Based Monitoring and Control System for Aquaponics Using IoT and Fuzzy Logic - Ranu Arga Noor Yuusufa; Nirwana Haidar Hari; Yudha Dwi Putra Negara; Khotibul Umam (ISAS, 2026)
Aquaponics integrates aquaculture and hydroponic cultivation to improve resource efficiency and support food security under constraints of limited land and water. Water quality is a critical determinant of aquaponics productivity; however, many small-scale systems still rely on manual and periodic monitoring, which limits timely intervention. This study proposes an Internet of Things (IoT)–enabled, web-based aquaponics monitoring and control system for catfish (Clarias gariepinus) cultivation integrated with water spinach (Ipomoea aquatica). The system acquires water quality parameters including temperature, pH, dissolved oxygen, and ammonia using multiple sensors connected to an Arduino Mega. Sensor data are transmitted in real time via an ESP communication module using the MQTT protocol through the HiveMQ broker and stored in a MongoDB database for real-time visualization and historical analysis. In addition, pump actuator control is implemented using fuzzy logic based on water temperature and ammonia concentration to regulate water circulation and provide an interpretable qualitative assessment of water quality. Experimental validation confirms reliable sensing, transmission, storage, and web-based monitoring in an aquaponics pond scenario. The end-to-end transmission delay from the microcontroller to the web application achieves an average of 0.369 s (369 ms), indicating near real-time performance suitable for continuous monitoring and control.